Influence of Linked Bridges on Thermally Activated Delayed Fluorescence Characteristic for DCBPy Emitter. Issue 9 (1st July 2019) - Gao, Ying; Yang, Xiao‐Dong; Wu, Shui‐Xing; Geng, Yun
Abstract: In this work, four compounds (2–5 ) are designed based on reportedDCBPy (1 ) to investigate the influence of linked bridges on thermally activated delayed fluorescence properties. The results indicate that2–5 have stronger oscillator strength and higher fluorescence radiative rate ( k r ) after introducing linked bridges. But, the increased local‐excitation and decreased charge‐transfer natures in the lowest singlet and triplet excited states lead to larger singlet‐triplet energy splitting (Δ Ε ST ) for2–5 than1 . The potential reverse intersystem crossing (RISC) channels are speculated for1–5 by considering the higher triplet excited state and spin‐orbit coupling (SOC) matrix element. It is concluded that the introduction of bridges noticeably enhances the SOC between singlet (S n ) and triplet (T n ) excited states. By analyzing the excited state energies and transition natures, 2 and3 are expected to undergo a T3 to S1 RISC process, and4 and5 are expected to undergo a RISC more significantly via T2 to S1 because of the almost equal energy levels and strong SOC. Abstract : Four compounds (2–5) are designed based on reported DCBPy (1) to investigate the influence of linked bridges on thermally activated delayed fluorescence properties. By employing density functional theory method, electronic properties including singlet‐triplet energy splitting, fluorescence radiative rate, spin‐orbit coupling matrix element, and potential reverse intersystem crossing channels are discussed.